Evidence based practice competence of future traditional Chinese medicine nurses: A cross-sectional online study. (March 2022) - Zhou, Fen; Lv, Yunpeng; Zhao, Junqiang
Abstract: Background: Previous studies demonstrated the low evidence-based practice competence of nurses in traditional Chinese medicine hospitals. University education may enhance nursing students' evidence-based practice competence. Few studies have investigated traditional Chinese Nursing Bachelor students' evidence-based practice competence. Objectives: To investigate the evidence-based practice competence of traditional Chinese Nursing Bachelor students across all grades and their influencing factors. Design: A cross-sectional online study. Settings: A traditional Chinese medicine university offering an evidence-based nursing curriculum in Beijing, China. Participants: A total of 601 traditional Chinese Nursing Bachelor students were recruited, with a response rate of 70.05%. The junior and senior groups consisted of first- and second-year students, and third- and fourth-year students, respectively. Methods: An online survey was conducted in 2019 using a self-administered questionnaire encompassing attitude, knowledge, and skill . A t -test, non-parametric test, and correlation analysis were used for data analysis. Results: Evidence-based practice attitude mean scores were the highest in both groups (3.87 ± 0.48 junior ; 3.97 ± 0.45 senior ), followed by skill (3.33 ± 0.46 junior ; 3.48 ± 0.46 senior ) and knowledge (3.21 ± 0.55 junior ; 3.52 ± 0.47 senior ). In the senior group, attitude decreased (from 4.02 to 3.86). The two groups reported the same items with the lowest scores in all three dimensions. The influencing factors were 1) scientific research experience ( Z = −2.87) and a medical literature retrieval course ( t = −3.40) for the junior group, 2) completion of the evidence-based nursing course ( Z = −2.59) for the senior group, and 3) student admission level ( Z junior = −2.55, Z senior = −3.85) and English language proficiency ( chi-square junior = 2.80, chi-square senior = 16.37) for both groups. Conclusions: Deficiencies in evidence implementation and decreasing evidence-based practice attitudes among fourth-year students warrant attention. Evidence-based nursing courses could be optimised, and research and English activities enriched to improve evidence-based practice competence. Highlights: Fourth-year students' EBP attitudes were lower than that of third-year students. Nursing curricula must be optimised to improve evidence implementation. Coaching should be extended to the clinical internship stage.